CDW-EIS theoretical calculations of projectile deflection for single ionization in highly charged ion-atom collisions - Rodríguez Chariarse, Vladimir Daniel (2003)
We present continuum distorted wave-eikonal initial state (CDW-EIS) theoretical calculations for the projectile deflection in single ionization of helium by heavy-ion impact as a function of ionized electron energies. These calculations account for the helium passive electron shielding in the internuclear interaction improving standard CDW-EIS theory. The results are compared with recent experimental results by impact of 100 MeV/amu C6+ and 3.6 MeV/amu Au53+. For highly charged projectiles there is a poor quantitative agreement between theory and experiment. However, this refined calculation does share some qualitative features with the data. In particular the variation of the effective charge of the residual He+ ion from Zeff = 1 to Zeff = 2 when going from small to large projectile scattering angles is able to represent a shoulder observed in the double differential cross sections. Important qualitative differences are observed at the level of triple differential cross sections. © 2003 Published by Elsevier Science B.V.